2015
DOI: 10.5301/hipint.5000257
|View full text |Cite
|
Sign up to set email alerts
|

Metal Ion Levels in Ceramic-on-Ceramic THR with Modular Necks: Analysis of Cobalt and Chromium Serum Levels in 30 Healthy Hip Patients

Abstract: The hybrid THR Profemur® Xm - Procotyl® L with a titanium modular neck on a cobalt-chrome stem design shows no signs of abnormal toxic ion levels (cobalt or chromium) in a randomly selected group of well-functioning hip patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Also, clinical results at long-term were good. We have shown that the systemic levels of Co and Cr in patients, treated with this cemented CoCr stem and a Ti modular neck, is low when used with conventional head diameters (18). In this study of asymptomatic high activity patients no patient was shown to have elevated Co ion levels and all patients had Cr ion levels below the detection limit.…”
Section: Discussionmentioning
confidence: 98%
“…Also, clinical results at long-term were good. We have shown that the systemic levels of Co and Cr in patients, treated with this cemented CoCr stem and a Ti modular neck, is low when used with conventional head diameters (18). In this study of asymptomatic high activity patients no patient was shown to have elevated Co ion levels and all patients had Cr ion levels below the detection limit.…”
Section: Discussionmentioning
confidence: 98%
“…The alarmingly high systemic Co levels, as measured in the serum of these patients with a CoCr femoral component, is probably due to the trunnion of the modular neck, since only the femoral component contains Co and Cr. We have shown that the systemic level of Co and Cr in modular necks of this design (Ti alloy neck coupled with a cemented CoCr stem) is low when used with conventional head diameters (23). In contrast with the results from Bosker et al (3), our results show no patients with osteolysis and a relatively low rate of ALTR (7.5%) at 3-year FU.…”
Section: Discussionmentioning
confidence: 98%
“…Two studies were published by Somers et al [ 24 , 25 ]. In the first study, 30 patients underwent THA with a hybrid THR Profemur ® Xm - Procotyl ® L prosthesis, with a Ti modular neck on a CoCr stem design and CoC bearing.…”
Section: Discussionmentioning
confidence: 99%